Fibrosis markers as prognostic markers of decline in kidney function in patients with neuroendocrine neoplasms undergoing peptide receptor radionuclide therapy - Stemann Lau, Tobias; Bossen, Lars; Rasmussen, Daniel Guldager Kring; Genovese, Federica; Karsdal, Morten; Arveschoug, Anne Kirstine; Grønbæk, Henning; Dam, Gitte (Frontiers in Endocrinology, 2025)
IntroductionDecline in kidney function due to renal fibrosis is a potential side effect in patients with neuroendocrine neoplasm (NEN) undergoing Peptide Receptor Radionuclide Therapy (PRRT). We aimed to investigate the potential of circulating fibrosis markers reflecting formation and degradation of collagens in predicting decline in kidney function in NEN-patients undergoing PRRT.Material and methodsWe included NEN-patients referred for PRRT treatment. We measured two biomarkers of type III and VI collagen formation, reflecting fibrogenesis (PRO-C3 and PRO-C6), and a degradation biomarker of type III collagen, reflecting fibrolysis (C3M) in serum and urine before initiation of PRRT and after each treatment. A kidney function test was performed before initiation of PRRT and three months after end of treatment (EOT) and when possible 6, 12, 18, and 24 months after EOT. We performed a linear mixed model to evaluate differences in the levels of fibrosis markers between patients who declined in kidney function vs patients who did not.ResultsFourteen patients (57% men and median age 67 years (IQR: 61-75)), completed PRRT treatment with at least one kidney function test following EOT. Median time from EOT to last kidney function test was 12 months (IQR: 12-21). Six patients (43%) experienced a more than 25% decline in kidney function from baseline to last kidney function test. For urinary (u) C3M, the overall linear mixed model was marginally significant (p = 0.078). Specifically, after the first treatment (74 ng/mg (95% CI: 49-113) vs 135 ng/mg (95% CI: 93-194)) and three months after EOT (56 ng/mg (95% CI: 37-86) vs 118 (95% CI: 81-173)), levels of uC3M were significantly lower in patients who subsequently had decline in kidney function.ConclusionAt specific time points, levels of uC3M significantly differed in patients who subsequently declined in kidney function. From these exploratory results, we believe that uC3M holds the potential as a prognostic biomarker, and we suggest that this should be further investigated in larger studies to draw firm conclusions about the usefulness.